The Influence of Motivation, Organizational Culture, Leadership Style, Conflict Management, on Job Satisfaction and Lecturer Performance at Universities in Southeast Sulawesi Province - Hardin H; Masdar Mas’ud; Zainuddin Rahman; Muchtar Lamo (Institute for Research and Community Service, 2021)
This study aims to (1) examine and analyze the positive and significant influence between motivation, organizational culture, leadership style and conflict management on lecturer job satisfaction. (2) To examine and analyze the positive and significant influence between motivation, organizational culture, leadership style and conflict management on lecturer performance. (3) To test and analyze the positive and significant effect of job satisfaction on lecturer performance. This study uses a quantitative approach by using primary data through questionnaires as many as 347 respondents from a population of 2578 lecturers. The study was conducted from November 2019 to January 2020. The data were analyzed using the SEM AMOS version 24.0 program. The results of this study indicate that: (1) Motivation has a positive and significant effect on job satisfaction. (2) Organizational culture has a positive and significant influence on job satisfaction. (3) Leadership style has a positive and significant effect on job satisfaction. (4) Conflict management has a positive and significant effect on job satisfaction. (5) Motivation has a positive but not significant effect on lecturer performance. (6) Organizational culture has a positive and significant influence on lecturer performance. (7) Leadership style has a positive and significant influence on lecturer performance. (8) Conflict management has a positive but not significant effect on lecturer performance. (9) Job satisfaction has a positive and significant effect on lecturer performance.